MENINGKATKAN KOMPETENSI MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI BIMBINGAN BERKELANJUTAN PADA GURU MIN 1 PESISIR SELATAN TP 2019/2020 - Sakirin, Sakirin (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
The problem in this research is the low capacity of teachers write lesson plans that conform to the standard process mdengan ketetan. While the task of one teacher is to plan learning well in order to achieve maximum learning goals. The aim of the study is to improve the ability to draw up a Learning Implementation Plan (RPP) through ongoing guidance to the MIN MIN 1 Pesisir Barat TP 2019/2020. The results showed in the first cycle the ability of teachers to reach a score of 37 or reached 52% and cycle II reached a score of 68 or reached 95%. Increasing from cycle to cycle reaches indicators of research success. Based on the results of this study it was concluded that the ability to draw up a Learning Implementation Plan (RPP) could be improved through ongoing guidance to Teachers MIN 1 West Coast TP 2019/2020.